XRD-DSC: a screening tool for identifying effective MOFs for selective gas sorption from humid gas streams. Issue 1 (7th February 2019) - Parise, John B; Chen, Xianyin; Plonka, Anna M.; Woerner, William R.; Banerjee, Debasis; Connors, David; Goroff, Nancy
Abstract : A commercially available combined X-ray diffraction – differential scanning calorimetry (XRD-DSC) stage was adapted for studies of gas loading in microporous materials, including metal organic frameworks (MOFs). Insertion of a custom-built humid atmosphere swing chamber (HASC) between a humidity generator and the XRD-DSC stage facilitates both humid atmosphere and vacuum swing gas loading. The HASC is necessary to buffer between the humidity generator and the XRD-DSC stage, allowing the gas mixture to homogenize prior to sample exposure, so that both humid atmosphere and vacuum swings could be performed. The changes in XRD can be used to follow structural changes, including collapse, which is indicative of a lack of microporosity upon activation, and the flexibity of frameworks upon gas sorption–desorption cycles. Measurements of the area under the DSC curve allows for calculation of the isosteric heat of adsorption ( Q st ; kJ molGAS −1 ). Vacuum-atmosphere swing experiments performed at different pressure steps allow for the reconstruction of the enthalpy of gas adsorption before and after a phase transition. These modes of operation are illustrated in three case studies from a program of exploratory MOF synthesis used to discover novel materials for selective gas sorption from humid gas streams: (1) gas binding in Stony Brook metal organic framework-1, (2) zeolitic imidazolate framework-7 response to variable pressure vacuum-atmosphere swing, and (3) high throughput evaluation of the selectivity of novel MOFs synthesized from customized linkers.